Health-related quality of life in TB patients: a narrative review - Tanwar, Deepika; Sikka, Gitanjali; Rajput, Meena; Kumar, Vipul; Meetu (International Journal of Research in Medical Sciences, 2025)
Tuberculosis (TB) continues to pose a substantial global health challenge, profoundly impacting patients’ health-related quality of life (HRQoL). This narrative review provides a comprehensive analysis of published research comparing HRQoL in individuals diagnosed with pulmonary tuberculosis (PTB) and extrapulmonary tuberculosis (EPTB). It delves into the nuanced differences in HRQoL experienced by these two patient groups, exploring physical, psychological, and social dimensions. Beyond comparing HRQoL outcomes, the review identifies key factors that influence these differences, such as disease severity, treatment duration, presence of comorbidities, and socioeconomic status. Furthermore, it examines the implications of these findings for clinical practice, including personalized treatment approaches, targeted support services, and strategies to address specific HRQoL challenges. Finally, the review highlights critical gaps in the current research and proposes potential directions for future studies, emphasizing the need for longitudinal research, standardized HRQoL assessment tools, and interventions aimed at improving the well-being of all TB patients, irrespective of disease presentation. By synthesizing existing evidence, this review aims to deepen our understanding of the distinct challenges faced by individuals with different forms of TB and inform the development of tailored interventions to optimize their overall well-being.